Variability of release parameters in basketball free throw - Nakano, N.; Fukashiro, S.; Yoshioka, S. (ISBS Proceedings Archive (Michigan), 2018)
The aim of this study is to clarify what kind of variability of release parameters is associated with shot accuracy in basketball free-throw. Eight male right-handed basketball players in college team participated in this study. Participants made 50 shots from the free-throw line after warm-up. A 16-camera motion capture system was used to record the coordinates of the reflective markers attached on the participants` bodies and the ball. The ball release parameters (i.e. release speed, angle and position) were calculated for the ball at the time of release. TNC-analysis that quantifies Tolerance, Noise, and Covariation cost of a performance (Cohen & Sternad, 2009; Sternad et al., 2011) and a correlation analysis were used to analyse the variability of release parameters. Our results showed that the value of C-cost is smaller for the participant whose shot probability of success was high. Our results suggest that learning various patterns of success in training may be efficient for improvement in free-throw.